Substrate induced dynamical remodeling of the binding pocket generates GTPase specificity in DOCK family of guanine nucleotide exchange factors - Roy, Debopriya; Sengupta, Durba; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2022)
Dedicator of cytokinesis (DOCK) family of guanine nucleotide exchange factors (GEFs) activate two members of Rho family GTPases, Rac1/Cdc42, to exert diverse cellular processes, including cell migration. As DOCK GEFs have been critically implicated in tumour cell migration, understanding their function and specificity is imperative for designing anti-metastatic drugs. Based on their GTPase specificity they have been classified as Rac, Cdc42 and dual specific GEFs. Despite extensive structural studies, the factors that determine GTPase specificity of DOCK GEFs have remained elusive. Here, we show that subtle dynamical coupling between GEF and GTPase structures modulate the binding interface to generate mutual spec-ificity. To cluster the dynamically coupled residues in GEF-GTPase complexes a novel intra-residue backbone-torsion-angles based mutual information (TMI) technique was employed. TMI was calcu-lated from 4500 trajectories obtained from a total of 4.5ms molecular dynamics simulations performed on members of all the three clades of DOCK GEFs. The obtained clusters suggest a specificity generation mechanism that involves optimization of the binding pocket for the crucial divergent residue at the 56th position of Rac/Cdc42 (FCdc42/WRac1). These clusters encompass five residues from the structural segment lobe C -a10 helix of the DOCK proteins and functional SWI region of GTPase, which induce orchestrated structural modulations to generate the specificity. Even the conserved residues from SWI region are seen to augment the specificity defining dynamical rearrangements. Furthermore, the pro-posed dynamical GTPase-DOCK GEF specificity model was verified using mutagenesis studies on Rac1 and dual GTPase specific Dock2 and Dock6, respectively. Thus the current study provides the generic substrate specificity determinants of DOCK GEFs, which are not apparent from the conventional struc-tural analysis.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: Dedicator of cytokinesis; GTPase specificity; Guanine exchange factors; Molecular dynamics simulations; Mutual information; Rho GTPases

Cocrystallization of multi-kinase inhibitor pazopanib with fenamic acids: improving dissolution and inhibiting cell migration - Rai, Sunil K.; Gunnam, Anilkumar; Roy, Debopriya; Rajput, Raveena; Kulkarni, Kiran; Nangia, Ashwini K. (CrystEngComm, 2023)
A multi-kinase inhibitor, pazopanib (PAZ) is cocrystallized with cyclooxygenase (COX) inhibitor fenamic acids to investigate the dissolution rate and inhibition of cell migration in VEGF-triggered HUVEC cells to test the efficacy of stoichiometric drug-drug combinations. Crystallization experiments at the sub-milligram level in an acetonitrile-methanol mixture yielded two drug-drug salt forms of PAZ with flufenamic acid (FFA) and niflumic acid (NFA) as PAZ+center dot FFA-center dot ACN (an acetonitrile solvate named as form I) and PAZ+center dot NFA-. Structures of the crystal forms were characterized by single crystal X-ray diffraction (SC-XRD) method. Crystal structures revealed that the presence of a 2-aminopyrimidine group in PAZ is a strong partner for the carboxyl group in all solid forms, forming an acidMIDLINE HORIZONTAL ELLIPSISpyrimidine heterosynthon with COX inhibitor fenamic acids. To perform dissolution experiments and cell line analysis, the scale-up of both salt forms were done in the acetonitrile-methanol mixture through crystallization, which showed a polymorphic transformation in the case of PAZ+center dot FFA-center dot ACN (an acetonitrile solvate named form II). The thermodynamic stability of PAZ+center dot FFA-center dot ACN (form II) and PAZ+center dot NFA- were analysed using slurry experiment under ambient conditions in pH 1.2 (0.1 N HCl) buffer medium and the residual solid phase was characterized by powder XRD, which showed that PAZ+center dot FFA-center dot ACN (form II) was a metastable solid form while PAZ+center dot NFA- was a stable solid form. The dissolution experiments at gastric pH 1.2 showed that the rate of dissolution of PAZ+center dot FFA-center dot ACN was 10 times higher than PAZ+center dot NFA-. The cell migration assay suggested that PAZ+center dot FFA-center dot ACN inhibited similar to 25% and PAZ+center dot NFA- inhibited similar to 20% migration of HUVEC cells compared to PAZ alone. These investigations suggested that the drug-drug salts PAZ+center dot FFA- and PAZ+center dot NFA- would be potential combo drug candidates for clinical trials. Multi-drug crystalline salts of pazopanib with fenamic acids exhibit enhanced dissolution and 20% higher inhibition in the migration of HUVEC cells compared to the reference drug.